Delineating profit gaps in rice and wheat production: Evidence from India's economically marginalized region - Anurag Ajay; Maxwell Mkondiwa; Anton Urfels; Daniel Müller (Agricultural and Food Economics, 2025)
Most farms in the Global South are small family farms and supporting these in generating ideal profits is critical for reducing poverty. We study the state of Bihar, the poorest in India where approximately 100 million people source their food and income from farms smaller than two hectares. Our research assesses the profit efficiencies achieved by smallholders in rice and wheat production and examine the variation in profit efficiencies across different farm sizes and geographical regions~of the state. Applying single-step stochastic profit frontier analysis with data from 4016 randomly selected farmers, we estimate profit potential and identify sources of profit inefficiency. Spatial mapping with profit efficiency scores helps visualize differences and pattern within the state. The findings reveal that high planting cost in wheat and high harvesting costs in rice and wheat reduce profit efficiency. Additionally, excessive rainfall in August and higher temperature in November impede profit efficiency of rice and wheat, respectively. The biggest source of inefficiency in rice and wheat production is costly diesel-driven irrigation system. Our estimates suggest that closing profit efficiency gaps can increase smallholder profits by 38% in rice and 35% in wheat. Identifying strategies to close profit gaps in smallholder settings and agriculture-led economies is crucial for informing interventions that alleviate rural poverty.
Keywords: 630; Bihar; Eastern India; profit efficiency; sources of inefficiency; stochastic frontier